The Influence of Project Based Learning Model on Students' Problem-Solving Competence in Learning of Acid-Base - Faizah, Nur; Wijayati, Nanik; Widiatningrum, Talitha (Journal of Innovative Science Education, 2022)
The study aims to determine the influence of Project Based Learning Model on students' problem-solving competency. The method used was experimental method with Pretest-Posttest Control Group Design. This study was conducted at the State Junior High School 2 Brebes with the students of grade VII in the academic year 2021/2022 as the research population. The sampling technique used in this study was Simple Random Sampling. The results showed that the average N-Gain Score for the experimental class was 0.76, it was higher than the control class with the score of 0.60. The results of the T-Test indicated that the data resulted in this study met the criteria with the value of tcount = 18,812 ˃ ttable = 1,97897 meaning that Ha is accepted. It can be concluded that the Project Based Learning Model has an influence on the students' problem-solving competence in learning acid-base.